The Dominant Effect of Profitability, Business Risk, Company Size and Leverage on Tax Avoidance with Good Corporate Governance as a Moderator - Rina Milyati Yuniastuti (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2024)
This study aims to prove which variable has the most dominant influence between the variable Profitability with a proxy for Return on Assets, Business Risk, Company Size/UP and Leverage with a debt-to-asset ratio (DAR) to ETR/Tax Avoidance. Corporate governance moderates variable profitability, business risk, firm size, and leverage with tax avoidance. Twenty-eight manufacturing companies were the object of research and listed on the IDX, and for three years, there were 84 companies as samples. The research method is a quantitative method that is analyzed using statistical applications. Meanwhile, based on statistical data, the results obtained on the variable Firm/UP Size have the most dominant influence compared to those studied on tax evasion. Meanwhile, the business risk variable with the most dominant tax avoidance with good corporate governance as a moderator has a role, while the leverage variable with tax avoidance with good corporate governance has no role. This research has implications in the field of financial ratios and taxation, and for further research